2006
DOI: 10.1103/physrevlett.96.034301
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear Emissions During Self-Nucleated Acoustic Cavitation

Abstract: A unique, new stand-alone acoustic inertial confinement nuclear fusion test device was successfully tested. Experiments using four different liquid types were conducted in which bubbles were self-nucleated without the use of external neutrons. Four independent detection systems were used (i.e., a neutron track plastic detector to provide unambiguous visible records for fast neutrons, a detector, a NE-113-type liquid scintillation detector, and a NaI gamma ray detector). Statistically significant nuclear emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…No modulation and pumping of protons, as described above for our case, were applied to the arc; therefore the conditions of the experiment were different from ours. On the other hand Taleyarkhan et al [3] and Nigmatulin et al [8] reported on gamma-ray emission from collapsed bubbles. In their experiments fast neutrons nucleated 30 bubble clusters per second in deuterated acetone; in self-nucleation experiments in which solute uranium salt emanated particles, the rate of creation of bubble clusters was much lower (for deuterated benzene-based mixtures and deuterated water).…”
Section: Gamma-radiationmentioning
confidence: 99%
See 4 more Smart Citations
“…No modulation and pumping of protons, as described above for our case, were applied to the arc; therefore the conditions of the experiment were different from ours. On the other hand Taleyarkhan et al [3] and Nigmatulin et al [8] reported on gamma-ray emission from collapsed bubbles. In their experiments fast neutrons nucleated 30 bubble clusters per second in deuterated acetone; in self-nucleation experiments in which solute uranium salt emanated particles, the rate of creation of bubble clusters was much lower (for deuterated benzene-based mixtures and deuterated water).…”
Section: Gamma-radiationmentioning
confidence: 99%
“…Nevertheless, in the experiments [2][3][4][5][6][7][8] the authors did not at all allude to heating of the liquids studied, which points to a kind of a nonradiative transition in nuclei in the small spherical zones mentioned above. In other words, the phenomenon of sonofusion may belong to the class of reactions known as low energy nuclear reactions, or cold fusion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations